The Nephroprotector Effect of Sukari Date (Phoenix dactylifera) Extract on Meloxicam Induced in Rats (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2022)
Drug poisoning in pets can cause serious kidney damage  due to high levels of free radicals in body against the toxicity. Prevention of kidney damage can be solved by using of some exogenous antioxidants. Sukari dates (Phoenix dactylifera) are reported able to reduce off free radicals with antioxidant active ingredients in such as flavonoids, phenolics, vitamins C, A, E, and B-carotene. This study aims to determine the effect of Sukkari date extract as a nephroprotector agent in reducing blood urea nitrogen (BUN) levels after meloxicam induced. This experimental study with a completely randomized design used 24 male white rats of wistar strain which were divided into 4 treatment groups. Group 1 (K1) is a negative control group given 1% NaCMC, group 2 (K2) is a positive control group given 2 ml at a dose of 30 mg/kgBW meloxicam, treatment group 1 (P1) and treatment group 2 (P2) were each given 2 ml of Sukari date extract at a dose of 500 mg/kgBW and 1000 mg/kgBW for 11 days. Meloxicam induction dose of 30 mg/kgBW was given on the 12th day, BUN levels were measured on the 13th day and 15th day with a spectrophotometer. BUN concentration of mean in control groups K1 was 19.54±0.828, K2 group was 41.55±0.534, the treatment group P1 was 24.86±0.715 and P2 was 20.48±0.383. These results indicate that the administration of Sukari date extract was able to maintain BUN levels at normal levels even though they had been exposed to toxic doses of meloxicam. Keywords: Antioxidants, Blood Urea Nitrogen (BUN), Sukkari dates, meloxicam